2023
DOI: 10.1117/1.jbo.28.12.121207
|View full text |Cite
|
Sign up to set email alerts
|

Frameworks of wavelength selection in diffuse reflectance spectroscopy for tissue differentiation in orthopedic surgery

Celina L. Li,
Carl J. Fisher,
Katarzyna Komolibus
et al.

Abstract: Wavelength selection from a large diffuse reflectance spectroscopy (DRS) dataset enables removal of spectral multicollinearity and thus leads to improved understanding of the feature domain. Feature selection (FS) frameworks are essential to discover the optimal wavelengths for tissue differentiation in DRSbased measurements, which can facilitate the development of compact multispectral optical systems with suitable illumination wavelengths for clinical translation.Aim: The aim was to develop an FS methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…[3][4][5] Several previous studies have explored the usage of DRS signals for the classification of tissues. Previous applications include the differentiation of tumorous and healthy tissue, [6][7][8] the classification of tissues, including those encountered during orthopedic procedures, [9][10][11][12][13] and the identification of tissue malignancies. 14 Based on these previous works it can be concluded that DRS is a viable method for the differentiation of tissues in both the binary and multiclass cases.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Several previous studies have explored the usage of DRS signals for the classification of tissues. Previous applications include the differentiation of tumorous and healthy tissue, [6][7][8] the classification of tissues, including those encountered during orthopedic procedures, [9][10][11][12][13] and the identification of tissue malignancies. 14 Based on these previous works it can be concluded that DRS is a viable method for the differentiation of tissues in both the binary and multiclass cases.…”
Section: Introductionmentioning
confidence: 99%